Les oiseaux de Bataille - Krzykawski, Michał (Romanica Silesiana)
Unlike Hitchcock, in Bataille there are no seagulls whose unusual behaviour would epitomize the inexplicable. And yet one may find countless birds in his texts. The aim of this article is to investigate what I call the “avian metaphor” in order to show that bird images are meant to convey fear originating from Bataille’s fantasized world and refer to the primal scene (Urszene) which represents his father with “huge, ever-gaping eyes that flanked an eagle nose.” I also endeavour to reveal the autobiographical background of what Bataille defines, in a more philosophical language, as angoisse (anguish/anxiety). Key words: autobiography, fantasy, trauma, horror, death